Tingkat Kepuasan Pemustaka Dalam Mengakses Layanan Digital Menggunakan Metode End User Computing Satisfaction Di UPT Perpustakaan Politeknik Negeri Padang - Ayu Septi Mulyani; Ardoni Ardoni (Journal of Creative Student Research, 2024)
The aim of this research is to describe the level of user satisfaction in accessing digital services at the Padang State Polytechnic Library UPT using the End User Computing Satisfaction (EUCS) method. This research is a quantitative type of research with a descriptive method through distributing questionnaires at the Padang State Polytechnic. The population in this study was 2,993 students with a sample size of 97 respondents. Sampling was determined based on the Simple Random Sampling technique, which is a sampling technique carried out randomly without paying attention to the starters in the population. The results of this research are that there is a level of user satisfaction in accessing digital services at the Padang State Polytechnic Library UPT using the EUCS method with 3 dimensions. First, the content dimension obtained an average score of 3.12 on a positive interval scale, that is, there is user satisfaction because digital services provide information that meets user needs. Second, the accuracy dimension obtained an average score of 3.08 on a positive interval scale, that is, there is also user satisfaction because digital services have accurate information such as accurate and trustworthy information. Third, the timeliness dimension obtained an average score of 3.08 in the positive interval, that is, there is also user satisfaction, because digital services provide the latest information and the desired information.